State of knowledge about biotechnological uses of digestive enzymes of marine fishery resources: a worldwide systematic review - Friedman, Ivana Soledad (2023)
The characterization of digestive enzymes presents in fish and their potential biotechnological uses is a well-developed and studied field. However, there has not been a systematic review that analyzes the state of knowledge of these enzymes at a global level. Therefore, a systematic literature search on three platforms was carried out to review and analyze existing knowledge about digestive enzymes of marine fishes from fisheries and aquaculture and their potential application in industrial processes. Using the PRISMA method for selecting journal manuscripts, we found 112 scientific articles published between 1984-2020 studying different digestive enzymes from 87 fish species. Most studies were carried out in Tunisia and Mexico and only 6 articles were published in South American countries. The most studied digestive enzymes were alkaline proteases, mainly trypsin, and the proposed uses for these enzymes were mainly as additives in commercial detergents. There is a vacancy in the characterization of other digestive enzymes as pepsins, lipases and amylases and the study of species that are distributed in the Southwest Atlantic Ocean. It is necessary to expand the knowledge about other digestive enzymes and to carry out new studies in regions with an important fishery development.